General route for the decomposition of InAs quantum dots during the capping process. (18th February 2016) - González, D; Reyes, D F; Utrilla, A D; Ben, T; Braza, V; Guzman, A; Hierro, A; Ulloa, J M
Abstract: The effect of the capping process on the morphology of InAs/GaAs quantum dots (QDs) by using different GaAs-based capping layers (CLs), ranging from strain reduction layers to strain compensating layers, has been studied by transmission microscopic techniques. For this, we have measured simultaneously the height and diameter in buried and uncapped QDs covering populations of hundreds of QDs that are statistically reliable. First, the uncapped QD population evolves in all cases from a pyramidal shape into a more homogenous distribution of buried QDs with a spherical-dome shape, despite the different mechanisms implicated in the QD capping. Second, the shape of the buried QDs depends only on the final QD size, where the radius of curvature is function of the base diameter independently of the CL composition and growth conditions. An asymmetric evolution of the QDs' morphology takes place, in which the QD height and base diameter are modified in the amount required to adopt a similar stable shape characterized by a averaged aspect ratio of 0.21. Our results contradict the traditional model of QD material redistribution from the apex to the base and point to a different universal behavior of the overgrowth processes in self-organized InAs QDs.